2006
DOI: 10.1007/s10958-006-0182-y
|View full text |Cite
|
Sign up to set email alerts
|

Generalized coherent states for oscillators connected with Meixner and Meixner—Pollaczek polynomials

Abstract: Hamiltonian which naturally arised in our formalism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In this section we discuss two examples, the Meixner-Pollaczek polynomials and the continuous Hahn polynomials, in their full generality. In our previous work on discrete quantum mechanics [14,15], only the special case of the Meixner-Pollaczek polynomials with the phase angle φ = π/2 and the special case of the continuous Hahn polynomials with two real parameters a 1 and a 2 are discussed, partly because these special cases of the two polynomials appear in several other dynamical contexts [6,3,2] and, in particular, they appear in the description of the equilibrium positions [19,13,14] of the classical Ruijsenaars-Schneider van Diejen systems [20,27].…”
Section: Hamiltonian Formulation For Dynamics Of Hypergeometric Orthomentioning
confidence: 99%
See 2 more Smart Citations
“…In this section we discuss two examples, the Meixner-Pollaczek polynomials and the continuous Hahn polynomials, in their full generality. In our previous work on discrete quantum mechanics [14,15], only the special case of the Meixner-Pollaczek polynomials with the phase angle φ = π/2 and the special case of the continuous Hahn polynomials with two real parameters a 1 and a 2 are discussed, partly because these special cases of the two polynomials appear in several other dynamical contexts [6,3,2] and, in particular, they appear in the description of the equilibrium positions [19,13,14] of the classical Ruijsenaars-Schneider van Diejen systems [20,27].…”
Section: Hamiltonian Formulation For Dynamics Of Hypergeometric Orthomentioning
confidence: 99%
“…For a ≤ 0, however, there appear other singularities of φ 0 (x; a), which break the hermiticity. The special case discussed in [14,6,2,3] is β = 0 or φ = π/2. The groundstate wavefunction φ 0 , as annihilated by the operator A, Aφ 0 = 0, is given by…”
Section: Meixner-pollaczek Polynomialsmentioning
confidence: 99%
See 1 more Smart Citation
“…One should mention that there are several similar studies in the literature [19][20][21][22][23][24][25][26] with multi-parameters deformed oscillators that do not necessarily obey the Fibonacci properties in the sense of the seminal paper by Arik [18] where the spectrum is given by a generalized Fibonacci sequence. They provide a unification of quantum oscillators with quantum groups [27][28][29][30][31], keeping the degeneracy property of the spectrum invariant under the symmetries of the quantum group. The quantum algebra with two deformation parameters may have a greater flexibility when it comes to applications in realistic phenomenological physical models [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In the last years the interest to studying of the oscillator-like systems (so-called "generalized oscillators") and to using such systems in various areas of quantum mechanics ( [1]- [3]) has significantly increased. In works [4]- [12] authors suggested a new approach to definition of generalized oscillators, connected with the given system of orthogonal polynomials and to construction of coherent states for these oscillators. Within the framework of this approach we investigated generalized oscillators, connected with classical orthogonal polynomials of a continuous argument (such as Laguerre, Legendre, Chebyshev, and Gegenbauer polynomials), orthogonal polynomials of a discrete argument (such as Meixner and Charlier polynomials) as well as systems connected with q-analogues of Hermite polynomials.…”
Section: Introductionmentioning
confidence: 99%